IMPLEMENTASI KEBIJAKAN PENUTUPAN DAN PENGGABUNGAN SEKOLAH DASAR NEGERI DILINGKUNGAN PEMERINTAHAN KOTA PEKANBARU (Studi Kasus di Sekolah Dasar Negeri 01 Pekanbaru) - Hasibuan, Tiffany Ramadhani; As’ari, Hasim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Pekanbaru City issued a policy of merging and closing public elementary schools in the government environment of Pekanbaru City in the efficiency of local government budgets. During the implementation at SDN 01, the parents of students at SDN 01 Pekanbaru were rejected. the parents of the students refused to merge schools, seeing the inadequate facilities and infrastructure. So that at the beginning of the implementation, students carried out teaching and learning activities at the mosque. The purpose of this study indicate the results of the implementation of a policy of closing and merging public elementary school in the government environment of Pekanbaru especially at SDN 01 Pekanbaru and showed limitations in the implementation of a policy of closing and merging public elementary school as found in the pekanbaru mayor's decision Number 289 in 2019. This research uses the theory of policy implementation by Van metter and Van Horn (2016) which uses 6 indicators, namely : Policy Standards and Objectives, Resources, Communication between organizations and implementing activities, Characteristics of implementing agencies, Socioeconomic and political conditions and disposition. This study used qualitative methods which are located in the city of Pekanbaru. Informants of this research that head of field elementary school at the service education of pekanbaru city and The principal of elementary school 1 pekanbaru and other relevant institutions by doing interviews, observations and documentation so that it gets the required data such as primary data and secondary data then analyzed showing the results of the implementation and its limitations. The results of this research found that implementation of a policy of closing and merging public elementary school in the government environment of Pekanbaru City has not been implemented to the fullest, caused by several inhibitory factors, Rejection of target group and adaptation between implementor and target group so that the implementation process does not run to the maximum. Keywords: Implementation, policy, Closing and Merging Public Elementary Schools